1975: la gloria della danza a Venezia, ovvero un sasso alieno gettato in laguna - Elisa Guzzo Vaccarino (Danza e Ricerca, 2023)
“Danza 75” burst onto the lagoon, surprisingly making Venice a focus of the art of the body in all-round performance. The straightforward and simple title of the event was chosen after discarding “Gloire de la danse” or “Gloire à la danse”. The Meetings-Show and the Academy-School had an international dimension, bringing together the classical, modern and ethnic worlds. They enlivened the summer in an Italy where ballet and dance suffered from minority and elitism. The project of the revitalising event for the lagoon city was entrusted by the Parisian UNESCO, committed to “Saving Venice”, to the hands of Maurice Béjart and Maurice Huisman, very active directors from the Théâtre de la Monnaie in Brussels. The main Venetian partners, "Biennale" and Fenice, will then become part of the project, supported by national and local political authorities. An unrepeatable unicum.